2000
DOI: 10.1046/j.1365-294x.2000.00884.x
|View full text |Cite
|
Sign up to set email alerts
|

Do discrepancies between microsatellite and allozyme variation reveal differential selection between sea and lagoon in the sea bass (Dicentrarchus labrax)?

Abstract: In the present study the genetic structure of Dicentrarchus labrax (14 samples from the Mediterranean) was analysed at six microsatellite loci, in order to test the hypothesis that some enzymatic loci undergo selection between marine and lagoon habitat. Eight of the 14 samples were analysed at both microsatellite and allozyme markers. The analysis of the genetic variation among the Mediterranean samples showed that (i)&Fcirc;ST values obtained with the six microsatellite loci were much smaller than those obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
134
1
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(148 citation statements)
references
References 45 publications
9
134
1
4
Order By: Relevance
“…On the other hand, the lack of significance in the AMOVA comparisons between groups could be also due to low power associate with a low number of populations per group such as was described by Fitzpatrick (2009). Therefore, according to our results from F ST values, Cavalli-Sforza genetic distances, correspondence analysis and significant genic and genotypic differentiation, we suggested that the highest genetic divergence observed between samples (Mazarrón and the rest of localities) could be consequence of the isolation of lagoonal populations from open sea which has been already reported in other coastal fishes such as Pomatoschistus minutus Berrebi et al 2009), Dicentrarchus labrax (Lemaire et al 2000), Atherina lagunae (Trabelsi et al 2004), Atherina boyeri (Kraitsek et al 2008;Milana et al 2012), Diplodus sargus (González-Wangüemert and Pérez-Ruzafa 2012) and several invertebrate species (Camilli et al 2001;González-Wangüemert et al 2006;Tarnowska et al 2010;Vergara-Chen et al 2010b).…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, the lack of significance in the AMOVA comparisons between groups could be also due to low power associate with a low number of populations per group such as was described by Fitzpatrick (2009). Therefore, according to our results from F ST values, Cavalli-Sforza genetic distances, correspondence analysis and significant genic and genotypic differentiation, we suggested that the highest genetic divergence observed between samples (Mazarrón and the rest of localities) could be consequence of the isolation of lagoonal populations from open sea which has been already reported in other coastal fishes such as Pomatoschistus minutus Berrebi et al 2009), Dicentrarchus labrax (Lemaire et al 2000), Atherina lagunae (Trabelsi et al 2004), Atherina boyeri (Kraitsek et al 2008;Milana et al 2012), Diplodus sargus (González-Wangüemert and Pérez-Ruzafa 2012) and several invertebrate species (Camilli et al 2001;González-Wangüemert et al 2006;Tarnowska et al 2010;Vergara-Chen et al 2010b).…”
Section: Discussionsupporting
confidence: 79%
“…Although still a controversial topic, balancing selection (or parallel evolution) has been identified as an important factor in the evolution of some marine species, for example, related to coral reef fishes (Gaither et al., 2015), European sea bass (Lemaire et al., 2000), and three‐spined stickleback (Feulner et al., 2013; Guo, DeFaveri, Sotelo, Nair, & Merilä, 2015). Moreover, it has also been suggested to play an important role in invasive processes of aquatic organisms (Vera, Díez‐del‐Molino, & García‐Marín, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a discrepancy between allozyme and microsatellite markers has been described in several marine species (Lemaire et al, 2000;De Innocentiis et al, 2001). It is indicative of either differentiation in one or both markers (Lemaire et al, 2000;De Innocentiis et al, 2001), suggesting that the observed differentiation was either due to selection or stochastic events (drift-gene flow) (De Innocentiis et al, 2001;McLean and Taylor, 2001). In our data set, microsatellite loci exhibited higher F ST values than allozyme loci, suggesting that the higher mutation rate in microsatellites has increased the allele frequency divergence among populations (Allendorf and Seeb, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the genetic structure of numerous organisms has been assessed using several kinds of estimators, resulting in the discovery of disparate levels of genetic differentiation for different markers (Pogson et al, 1995;Lemaire et al, 2000;but see, Allendrof and Seeb, 2000). Although allozymes are still widely used, microsatellites have gained in importance due to their high levels of polymorphism, which facilitates the discovery of subtle differentiation (Ruzzante et al, 1998;Shaw et al, 1999).…”
Section: Introductionmentioning
confidence: 99%